Communication and Interaction Model for e-Learning Courses in Higher Education (Docentes 2.0 Journal, 2022)
Communication and interaction through virtual courses. Higher education has chosen to offer courses both in face-to-face mode and in a virtual manner to provide a broad panorama of the educational field. The objective of this research has been, on the one hand, to highlight the importance of integrating a counseling plan through interaction and communication between teacher and student in e-learning courses and the other hand, to detect the problems that exist with the exercise. The descriptive method was used under the positivist paradigm, with a quantitative approach, experimental design, and correlational type to demonstrate the instrument type questionnaire with 53 items. The measurement scale used in the questions was a 5-point Likert scale with the variables of interaction and follow-up, and advice. This questionnaire was applied to professors of the Faculty of Informatics of the Autonomous University of Querétaro. For the processing and analysis of the data, the measurement of Cronbach's Alpha was used, which resulted in 0.947, being reliable to continue with the investigation. The results showed an absence in the implementation of advisory plans to address student doubts, being an essential factor within the monitoring variable. This leads to the proposal of communication and interaction strategies between teacher and student to develop an excellent teaching-learning process.
Keywords: Higher education; learning; e-learning; instructional design